EVALUATION OF HYPOGLYCEMIC AND HYPOLIPIDEMIC EFFECTS OF INTERNAL SEPTUM OF WALNUT FRUIT IN ALLOXAN-INDUCED DIABETIC RATS - Ghiravani, Zahra; Hosseini, Mehran; Taheri, MohamadMehdi Hassanzadeh; Fard, Mohammad Hassanpour; Abedini, Mohammad Reza (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Todays, the popularity of herbal medicine is increasing worldwide. Due to importance the evaluation of medicinalherbs efficacy and safety, the present study was conducted to investigate the antidiabetic and hypolipidemic effects of internalseptum of walnut fruit (ISWF) ethanolic extract in diabetic rats.Materials and methods: Alloxan diabetic rats treated orally with ethanolic extract of ISWF (0-400mg/kg) for 28 days. To evaluateits anti-diabetic activity, the animals fasting blood glucose were determined on the first, 14th and 29th days. Moreover, oral glucosetolerance test (OGTT) was performed in diabetic rats at the last day of the study. After 24h of last administration, the blood sampleswere collected, and the Plasma lipids and liver enzymes levels were measured in fasting overnight rats.Results: The extract significantly decreased blood glucose (p<0.001) on 14th and 29th days. In addition, OGTT revealed that thehypoglycemic effect of the extract appeared at 90 minutes. Alanine aminotransferase and aspartate aminotransferase levelssignificantly decreased in diabetic rats treated with the both doses (p<0.05). Both doses of the extract were able to decreasetriglyceride significantly (p<0.05) in treated diabetic rats, while only the lower dose of the extract (200 mg/kg) attenuate the totalcholesterol and low density lipoprotein (p<0.001).Conclusion: These finding support the notion that ISWF is able to reduce hyperglycemia and hyperlipidemia risk in diabetic rats.